Torpix The Twisting Serpent : The Warlock's Staff - Blade, Adam (London : Orchard Books, 2011)
If Malvel takes the Warlock's Staff to the Eternal Flame, he will rule all lands forever. But there is one more Beast to battle: Torpix the Twisted Serpent! Only by defeating both Torpix and Malvel will Tom fulfill his Quest
Keywords: Children's Literature - Fiction : Fantasy